Effect of Mytilus coruscus selective filtration on phytoplankton assemblages - Jiang, Tao; Pan, Huizhu; Steeves, Laura; Jiang, Zengjie; Filgueira, Ramón; Strand, Øivind; Strohmeier, Tore; Cranford, Peter J.; Cui, Zhengguo (Frontiers in Marine Science, 2022)
Feeding selectivity of bivalves may impact phytoplankton biomass and community structure in the natural environment. Particle selection of natural algal assemblages by suspension feeders has typically been studied by using microscopic methods. In this study, we investigated the feeding selectivity of blue mussels Mytilus coruscus on natural phytoplankton assemblages in Sungo Bay using both optical microscopy and HPLC-pigment analysis. Results showed that cryptophytes dominated the phytoplankton community and made up 66.1% of the total phytoplankton abundance. A comparison of phytoplankton composition between natural and filtered seawater showed that M. coruscus preferentially cleared the cryptophytes and dinoflagellates while ingesting less Chaetoceros spp. and Skeletonema spp. Stomach analysis showed cryptophytes were not found by microscopic observation while their marker pigment alloxanthin was present, which indicates that cryptophytes can be ingested and easily digested. The proportion of Chaetoceros spp. and Skeletonema spp. in gut contents was significantly lower than in the seawater while that of Cocconeis spp. and Pinnularia spp. showed the opposite results. M. coruscus is much more efficient in removing larger algae than pico-phytoplankton, but the presence of prasinoxanthin and zeaxanthin (marker pigments of prasinophytes and Synechococcus, respectively) in gut contents suggested that pico-plankton is also a food source for this bivalve.